Mortise structure graphite coating combined bearing processing technology

CN120962287BActive Publication Date: 2026-11-03SHANGHAI HYDRA MASCH MFG CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511063360.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-30
Publication Date
2026-11-03
Estimated Expiration
2045-07-30

AI Technical Summary

Technical Problem

The existing mortise and tenon bearing processing suffers from problems such as poor assembly accuracy due to inconsistent initial temperatures, significant heat-affected zone from laser cutting, inadequate cleaning and surface treatment, and a lack of systematic process flow, all of which affect processing accuracy and performance reliability.

Method used

The process involves low-temperature freezing, laser directional cutting, plasma cleaning, nano-coating, and multi-stage heat treatment, including low-temperature freezing, laser directional cutting, plasma cleaning, high-frequency heating and nano-coating, medium-temperature heat treatment, and high-temperature tempering and oil bath cooling, to ensure material consistency and surface cleanliness.

Benefits of technology

It achieves high fitting precision, uniform heat treatment, and surface cleanliness in mortise and tenon structure bearings, improves machining accuracy and performance stability, and solves problems such as cutting deformation, thermal stress damage, and interface contamination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120962287B_ABST
    Figure CN120962287B_ABST
Patent Text Reader

Abstract

The application discloses a tenon-and-mortise structure graphite coating combined bearing machining process, which comprises six steps of low-temperature freezing treatment, laser directional cutting, plasma cleaning, high-frequency heating and nano spraying, medium-temperature heat treatment, high-temperature tempering and oil tank cooling. The structure cutting precision is improved by controlling the temperature and humidity stability in the freezing stage, combining the laser cutting path error control and the heat affected zone monitoring. The surface cleanliness and the coating adhesion performance are improved by adopting the mixed gas plasma cleaning and the nano graphite spraying. The structure thermal stability and the assembly adaptability are realized by the multi-section temperature control heat treatment and the precise cooling parameter management. The process parameters are clear and the steps are controllable, and the application is suitable for the precision manufacturing of high-performance tenon-and-mortise structure bearings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of precision machining technology, specifically to a machining process for a graphite-coated composite bearing with a tenon and mortise structure. Background Technology

[0002] Due to its structural characteristics such as self-centering, shear resistance, and repeatable assembly, the mortise and tenon structure has been introduced into modern precision manufacturing to improve the structural fit of bearing assemblies, and is especially suitable for applications requiring threadless connections and precise positioning.

[0003] However, in the current technology, the machining accuracy of mortise and tenon structure bearings still faces significant challenges: Inconsistent initial temperature of components: Lack of pretreatment or temperature equalization of raw materials leads to uneven thermal expansion and contraction during cutting and heat treatment, affecting the final assembly accuracy. The laser cutting process has a large heat-affected zone: unstable laser power, path planning and workpiece alignment cause the heat-affected zone to expand, edge ablation, and microcrack generation, affecting the integrity of the joint surface; The cleaning and surface treatment processes are lagging behind: traditional chemical cleaning leaves behind corrosion residues and poor coating adhesion, which cannot meet the assembly requirements of high cleanliness and high adhesion. Uneven heat treatment: Lack of staged heat treatment logic, grain coarsening or insufficient release of microstructure stress, resulting in structural deformation or performance fluctuations after assembly; Lack of a complete and systematic process flow: The lack of precise parameter linkage between each step results in poor process controllability, poor repeatability, and difficulty in industrialization.

[0004] Therefore, there is an urgent need for a complete processing technology that includes pretreatment, precise cutting, clean spraying, and multi-stage thermal control, in order to achieve structural precision control and performance reliability assurance of tenon and mortise bearings during the manufacturing process. Summary of the Invention

[0005] The purpose of this invention is to provide a processing technology for graphite-coated composite bearings with mortise and tenon structures, which has the advantages of high fitting accuracy, uniform heat treatment, high surface cleanliness, and strong structural stability, and solves the problems of cutting deformation, thermal stress damage and interface contamination existing in the prior art.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a processing technology for a graphite-coated composite bearing with a tenon and mortise structure, comprising the following steps: Step S1) Low-temperature freezing treatment; Step S2) Laser directional cutting; Step S3) Plasma cleaning treatment; Step S4) High-frequency heating and nano-spraying; Step S5) Medium-temperature heat treatment; Step S6) High-temperature tempering and oil bath cooling treatment.

[0007] Preferably, step S1) low-temperature freezing treatment includes: S11. Place all the metal parts of the tenon and mortise structure bearing into a freezer at a temperature of -18℃ to -25℃, and control the temperature of the parts to be uniform until the preset freezing temperature is reached. S12. Freezing time is not less than 24 hours to maintain material structural stability, release internal stress, and avoid deformation due to temperature difference. S13. Temperature fluctuations during the freezing process are controlled within ±1℃, and the freezing environment is maintained stable by a temperature and humidity control device.

[0008] Step S2) laser directional cutting includes: S21. Place the frozen bearing parts on a CNC laser cutting platform, with an alignment error not exceeding 0.1 mm; S22. Perform high-precision cutting according to the drawings of the mortise and tenon structure, and control the path error within ±0.05 mm; S23, laser power is set to 20-50 W, cutting speed is 5-10 mm / s; S24. After cutting, a vision system and measuring instruments are used to check the accuracy, and the cut surface meets the design requirements.

[0009] Step S3) plasma cleaning includes: S31. Place the cut bearing components into a plasma cleaning tank to fully expose their surfaces to the treatment area. S32. Set the cleaning power to 100-200 W and the time to 5-15 minutes. S33. After the treatment is completed, the surface cleanliness is confirmed by visual inspection and instrument testing.

[0010] Step S4) High-frequency heating and nano-spraying includes: S41. Place the component into the high-frequency induction heater, set the heating temperature to 250-400℃, and the heating time to 5-10 minutes; S42. During the heating process, GC-901 nano-graphite material is sprayed using a gas spraying method; S43. Allow to cool naturally to room temperature after spraying.

[0011] The intermediate temperature heat treatment in step S5) includes: S51. Place the cooled components in a constant temperature chamber, set the temperature to 100-150℃, and maintain it for 4-6 hours. S52. Temperature fluctuations during the constant temperature process shall not exceed ±2℃; S53. After processing, the structural morphology and mechanical properties are tested.

[0012] Step S6) High-temperature tempering and oil bath cooling treatment includes: S61. Place the parts treated at medium temperature into a high-temperature tempering chamber, set the temperature to 250-350℃, and the tempering time to 2-4 hours. S62. After tempering, transfer the parts into the oil bath. The oil temperature is controlled at 25-50℃ and the cooling rate is 5-10℃ / min. S63. After cooling, degreasing is performed using an environmentally friendly industrial cleaning agent. The surface moisture content is controlled below 0.5% after cleaning.

[0013] Preferably, in step S13, three temperature monitoring points are set inside the freezer, located at different spatial positions of the bearing components, and the temperature fluctuation is controlled within ±0.5℃. The relative humidity in the freezing environment is maintained at 20% to 40%, and the humidity is controlled by the dehumidification module.

[0014] Preferably, in step S22, the laser cutting path is obtained by automatically fitting the three-dimensional modeling results of the mortise and tenon structure, and the path accuracy control error does not exceed ±0.03 mm; The laser wavelength is 1064 nm, the focused spot diameter is set to 60–80 μm, and the width of the heat-affected zone is monitored and controlled in real time within the range of 0.05–0.1 mm.

[0015] Preferably, in step S32, the plasma cleaning uses a mixed gas with an argon-oxygen volume ratio of 9:1 as the working medium, and the flow rate is controlled at 200-300 mL / min. The cleaning time is set to 10-15 minutes, and the plasma field strength is maintained at 50-80 V.

[0016] Preferably, in step S42, the particle size of the GC-901 nano-graphite material is less than 50 nm, the gas spraying pressure is set to 0.2-0.4 MPa, and the spraying distance is set to 25±2 cm. The thickness of the coating layer should be controlled between 20 and 50 μm, and the natural cooling time after spraying should be set to no less than 30 minutes.

[0017] Preferably, in step S51, the medium-temperature heat treatment uses a constant temperature chamber with the temperature controlled at 100-150°C, and the treatment time is set to 4-6 hours. The surface temperature of the workpiece is collected every 30 minutes, and the temperature fluctuation range is controlled within ±2℃.

[0018] Preferably, in step S63, high-purity mineral oil is used for oil tank cooling, the oil temperature is set to 30±2℃, and the cooling time is set to 10 to 15 minutes; The cleaning process uses ultrasonic waves at a frequency of 40 kHz for 2 to 3 minutes. The drying process uses 45°C hot air to dry for 60 seconds, and the moisture content is controlled to be below 0.5%.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention improves heat treatment consistency by setting a low-temperature freezing pretreatment step, placing bearing components in an environment of −18℃ to −25℃ for more than 24 hours of stable freezing, controlling humidity and temperature fluctuations, reducing internal stress and unifying the initial state of materials. During the laser directional cutting process, a CNC platform is used for precise alignment, combined with a 1064 nm infrared laser and a path fitting algorithm to control the laser error to no more than ±0.05 mm. At the same time, the width of the heat-affected zone is monitored in real time to keep the cut surface edges clean and free of cracks and burrs. The cleaning process uses argon-oxygen mixed plasma to control the gas ratio, flow rate and field strength, effectively removing the surface contaminant layer and improving cleanliness. Subsequently, GC-901 nano-graphite is used for uniform spraying to enhance lubricity and bonding surface stability. The heat treatment process is divided into two stages: medium-temperature stabilization treatment and high-temperature tempering + oil bath cooling. By step-by-step temperature control, constant temperature maintenance and cooling rate management, the microstructure transformation path is optimized, the grain uniformity and deformation resistance are improved, and finally, a mortise and tenon joint bearing component with stable structure and controllable precision is formed. Attached Figure Description

[0020] Figure 1 This is a flowchart illustrating the overall processing technology of the graphite-coated composite bearing with mortise and tenon structure according to the present invention. Figure 2 This is a schematic diagram of the directional laser cutting structure of the present invention; Figure 3 This is a schematic diagram of the plasma cleaning process of the present invention; Figure 4 This is a schematic diagram of the high-frequency heating and spray coating thickness control of the present invention; Figure 5 This is a flowchart of the high-temperature tempering and oil tank cooling process of the present invention. Detailed Implementation

[0021] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0022] Please see Figures 1 to 5 This invention proposes a graphite-coated composite bearing manufacturing process with mortise and tenon joints, applicable to the manufacturing of mortise and tenon joint bearing components requiring high fitting precision and structural stability. The process uses bearing components as the processing object, sequentially undergoing low-temperature freezing, laser directional cutting, plasma cleaning, high-frequency heating and nano-spraying, medium-temperature heat treatment, high-temperature tempering, and oil bath cooling to form a mortise and tenon joint component with a complete structure, uniform heat treatment, and clean mating surfaces.

[0023] Please see Figure 1 The overall processing flow of this invention is as follows: Step S1) Low-temperature freezing treatment: Pre-treat the bearing components in a low-temperature environment to release internal stress; Step S2) Laser directional cutting: Precision laser cutting is performed on the frozen parts to form mortise and tenon joints; Step S3) Plasma cleaning treatment: Removes post-cutting residue and surface micro-contamination; Step S4) High-frequency heating and nano-spraying: Perform local surface functional enhancement treatment; Step S5) Medium-temperature heat treatment: Stabilizes the material structure and further releases residual stress; Step S6) High-temperature tempering and oil bath cooling: Complete the final heat treatment and cleaning process to obtain the finished product.

[0024] The above steps are executed sequentially according to a set order, and the process parameters for each step are adjustable and industrially feasible. Specifically: Step S1) Low-temperature freezing treatment This step aims to pre-treat all metal components of the tenon-and-mortise bearing structure, reduce internal stress and initial thermal expansion and contraction differences, and provide a uniform initial material state for subsequent precision cutting and heat treatment.

[0025] The specific steps are as follows: The entire bearing assembly is placed in a sealed package, preferably made of polyethylene, and filled with dry nitrogen to create a moisture-proof environment. The sealed assembly is then placed in a cryogenic freezer at a temperature of -18°C to -25°C for freezing. The assemblies should be evenly distributed within the freezer to avoid overlapping and ensure consistent cooling.

[0026] The freezing time is set to be no less than 24 hours. During this period, three temperature monitoring probes are installed inside the freezer, located at the top, middle, and bottom of the unit, respectively, to record temperature changes in real time and provide feedback adjustments. Temperature fluctuations during the freezing process are controlled within ±1℃, preferably within ±0.5℃. The relative humidity of the freezing environment is maintained between 20% and 40%, automatically regulated by the dehumidification module to prevent frost or condensation from corroding or contaminating the surfaces of metal components.

[0027] After the freezing process is completed, the parts are removed and moved directly to the next step, without being exposed to room temperature, in order to maintain the cold conditions of the materials.

[0028] Step S2) Laser directional cutting Bearing components that have undergone cryogenic freezing are immediately transferred to the laser cutting area while remaining cold. The cutting operation is performed on a CNC laser cutting platform equipped with automatic alignment, path import, and real-time monitoring functions.

[0029] First, the bearing components are placed on the laser cutting platform according to the machining reference surface. The platform has a three-axis leveling structure, and the alignment error is controlled within 0.1 mm. The cutting path is preset according to the CAD structural drawing of the mortise and tenon joint interface, and a high-resolution fitting curve is generated through the 3D modeling module. The cutting path is imported into the platform control system before execution and is corrected for errors with the actual clamping posture, with the path deviation controlled within ±0.05 mm.

[0030] Laser cutting utilizes an infrared laser source with a wavelength of 1064 nm, a focused spot diameter controlled between 60 and 80 μm, a laser power set between 20 and 50 W, and a cutting speed set between 5 and 10 mm / s. During the cutting process, the platform control system monitors the width of the heat-affected zone (HAZ) in real time and controls it within the range of 0.05 to 0.1 mm to ensure minimal thermal damage at the cut boundary.

[0031] Immediately after cutting, the cut surface undergoes quality inspection. First, a high-magnification industrial camera is used for visual inspection to determine if there are defects such as ablation, burrs, or chipping on the edges. Then, a digital micrometer and surface roughness tester are used to measure the dimensional accuracy and flatness of key mating parts to confirm that the cut surface meets the design requirements of the drawings.

[0032] After this step is completed, the parts will be transferred to the next process for surface cleaning.

[0033] Step S3) Plasma cleaning treatment After initial inspection, the laser-cut bearing parts are immediately transferred to the plasma cleaning area to remove cutting residues and surface contaminants.

[0034] The components are placed in a plasma cleaning tank, which is a closed plasma treatment device equipped with a working chamber, a gas input module, a high-frequency power supply system, and a plasma excitation device. The bearing components are fixed in the cleaning tank with tooling fixtures to ensure that their exposed surfaces can be fully treated.

[0035] The working gas used is a mixture of argon and oxygen in a volume ratio of 9:1, with the total gas flow rate controlled at 200–300 mL / min. The gas enters the processing chamber after precise adjustment by a mass flow controller, forming a stable plasma atmosphere. The plasma field strength is set to 50–80 V, and the cleaning time is controlled at 10–15 minutes, depending on the degree of surface contamination in the cutting area.

[0036] During the cleaning process, plasma creates a synergistic effect of physical bombardment and chemical oxidation on the metal surface, removing surface debris, laser slag, carbonized layer and grease residue. The treated surface has good activity and cleanliness.

[0037] After cleaning, the components were removed and their surface condition was inspected. The inspection combined visual inspection with industrial microscopy to check for any residue adhesion, discoloration areas, or foreign matter residue; at the same time, a surface contamination test cloth was used for wiping and comparison to confirm that there were no obvious particles or oil stains remaining.

[0038] Once the components have been processed, they can be directly transferred to the next process for surface functional enhancement.

[0039] Step S4) High-frequency heating and nano-spraying After plasma cleaning, the bearing components enter the surface functional enhancement stage. Through high-frequency induction heating combined with the spraying of nano-graphite materials, a lubrication guide layer is formed, which enhances the wear resistance and stability of the bonding area.

[0040] First, the cleaned bearing components are fixed in the working chamber of the high-frequency induction heater. The heater uses a medium-frequency induction coil system, which has non-contact heating characteristics. The heating temperature is set to 250–400℃, and the heating time is controlled to be 5–10 minutes. During the heating process, the component temperature is regulated by thermocouple feedback to ensure a uniform heating rate and avoid local overheating.

[0041] After reaching the target temperature, the gas spraying system is activated to apply nanomaterials to the mating surfaces of the components. The material used is GC-901 nano-graphite material with a particle size of less than 50 nm. The spraying air pressure is set to 0.2–0.4 MPa, the distance from the nozzle to the workpiece surface is set to 25 ± 2 cm, and the spraying angle is controlled at 90° ± 5°.

[0042] The spraying process is divided into multiple short-duration progressive modes, with each spray thickness controlled between 0.1 and 0.3 mm, and the total spray thickness between 20 and 50 μm, ensuring a uniform, continuous, and firmly adhered coating. After spraying, heating is immediately stopped, and the parts are allowed to cool naturally in a cleanroom environment with the ambient temperature controlled between 20 and 25°C.

[0043] The natural cooling time is set to no less than 30 minutes. After the coating cools, no post-treatment is performed to ensure its surface integrity and structural activity. The final graphite coating surface is uniformly gray-black, without cracks, peeling, or particle aggregation.

[0044] After the coating is completed, the parts are directly transferred to the next step for medium-temperature heat treatment.

[0045] Step S5) Medium-temperature heat treatment After the bearing components undergo high-frequency heating and nano-graphite spraying treatment are naturally cooled, they are transferred to a medium-temperature heat treatment process to further stabilize their crystal structure, release residual stress, and improve the uniformity and dimensional stability of the material structure.

[0046] The component is placed inside the incubator and supported by a high-temperature resistant fixture to prevent direct contact with the heating plate and the creation of localized hot spots. The incubator temperature is set to 100–150°C and maintained for 4–6 hours. The heating rate is set to 3–5°C / min to ensure a uniform internal temperature gradient.

[0047] During the heat treatment process, the constant temperature chamber is equipped with a multi-point thermocouple real-time monitoring device to continuously collect temperature data at multiple key locations of the bearing components. The sampling frequency is once every 30 minutes, and the temperature fluctuation range is controlled within ±2℃. The system automatically performs temperature compensation and adjustment to ensure a stable and consistent temperature distribution throughout the constant temperature section.

[0048] After heat treatment, the parts are slowly and naturally cooled to room temperature to avoid thermal stress concentration or microcrack formation caused by sudden cooling. After the parts are removed, structural inspection fixtures are used to re-inspect their dimensions, changes in aperture, and surface condition. A microhardness tester is used to randomly check the surface micro-area hardness to confirm that the heat treatment effect meets the standards.

[0049] After this step is completed, the component enters the final high-temperature tempering and oil bath cooling process.

[0050] Step S6) High-temperature tempering and oil bath cooling treatment Bearing components that have completed medium-temperature heat treatment and passed inspection will enter the final heat treatment and cooling cleaning stage to improve the overall material structure stability and the cleanliness of the mating surfaces.

[0051] The bearing components, after medium-temperature treatment, are immediately transferred to a high-temperature tempering chamber for further heating. The high-temperature tempering chamber is a closed-type electric heating and temperature control device with a multi-point temperature control feedback system. The tempering temperature is set to 250–350℃, the heating time is 2–4 hours, the heating rate is controlled within 5℃ / min, and the temperature fluctuation in the constant-temperature section is maintained within ±3℃.

[0052] After high-temperature tempering, the components are immediately removed and immersed in an oil bath for rapid cooling. High-purity mineral cooling oil is used as the cooling medium, with the oil temperature set at 30±2℃. During cooling, a stirring mechanism maintains a uniform oil temperature distribution. The cooling rate is controlled at 5–10℃ / min, and the cooling time is set at 10–15 minutes, until the overall temperature of the components drops below room temperature.

[0053] After cooling, the component surface often retains oil film, graphite residue, and adsorbed particles, requiring post-treatment cleaning. Cleaning is performed using an environmentally friendly industrial cleaning agent in conjunction with an ultrasonic cleaning system. The ultrasonic frequency is set to 40 kHz, and the cleaning time is 2–3 minutes to remove the adsorbed layer. After cleaning, the components are dried using 45°C hot air for 60 seconds.

[0054] The final surface moisture content was less than 0.5%, and the cleaned mating surfaces were free of oil stains, residual film, and particulate matter, meeting the high cleanliness requirements for assembly. After completing this step, a finished bearing meeting the assembly precision requirements of the mortise and tenon structure was obtained.

[0055] To verify the effectiveness of the graphite coating composite bearing processing technology with mortise and tenon structure described in this invention, a series of experiments were conducted in this embodiment. Multiple comparative experiments were performed on each key step (low-temperature freezing treatment, laser directional cutting, plasma cleaning, nano-spraying, high-temperature tempering, and oil bath cooling), and the performance indicators of the final product were quantified. By controlling the influence of different parameters on the processing results, the optimal combination of process parameters was finally determined.

[0056] Example 1: Experiment on the machining process of mortise and tenon structure bearings Experimental Background To verify the effectiveness and superiority of the mortise and tenon structure graphite coating composite bearing processing technology described in this invention, a series of experiments were conducted to compare the effects of different process conditions on bearing performance in key steps such as low-temperature freezing, laser cutting, plasma cleaning, high-frequency heating and spraying, medium-temperature heat treatment, and high-temperature tempering.

[0057] Experimental steps Low-temperature freezing treatment (S1): Objective: To release internal stress and unify the initial state of component materials.

[0058] parameter: Freezing temperatures: −20℃, −22℃, −25℃ Freezing time: 24 hours, 26 hours, 22 hours Equipment: Use a temperature and humidity controllable freezer, with the relative humidity of the freezing environment controlled between 20% and 40%.

[0059] Laser directional cutting (S2): Objective: To precisely cut the mortise and tenon joint surfaces to ensure connection accuracy.

[0060] parameter: Laser power: 30 W, 40 W, 25 W Cutting rates: 7 mm / s, 6 mm / s, 8 mm / s Equipment: CNC laser cutting platform, with cutting error controlled within ±0.05 mm.

[0061] Plasma cleaning process (S3): Objective: To remove surface residue, oil, and contaminants, and improve cleanliness.

[0062] parameter: Gas volume ratio: argon:oxygen 9:1, flow rate controlled at 200 mL / min to 300 mL / min Cleaning time: 10 minutes, 15 minutes Plasma field strength: 50V, 80V Equipment: Plasma cleaning tank.

[0063] High-frequency heating and nano-spraying (S4): Objective: To provide a wear-resistant coating to the bearing surface and enhance structural strength.

[0064] parameter: Heating temperatures: 300℃, 320℃, 350℃ Coating thickness: 30 μm, 40 μm, 50 μm Spraying air pressure: 0.2 MPa, 0.4 MPa Equipment: High-frequency heater and gas spraying system.

[0065] Medium-temperature heat treatment (S5): Objective: To stabilize the metallic crystal structure and release residual stress.

[0066] parameter: Heat treatment temperatures: 130℃, 140℃, 120℃ Heating time: 5 hours, 4 hours, 6 hours Equipment: Constant temperature chamber, with temperature fluctuations controlled within ±2℃.

[0067] High-temperature tempering and oil bath cooling (S6): Objective: To further enhance the material microstructure and improve dimensional stability.

[0068] parameter: Tempering temperatures: 300℃, 350℃, 320℃ Cooling rates: 5℃ / min, 10℃ / min Oil bath temperature: 30℃, 35℃ Equipment: High-temperature tempering chamber, oil tank cooling system.

[0069] Experimental Results and Performance Comparison After each step, key performance indicators such as hardness, dimensional accuracy, and surface roughness of the finished product were measured. The experimental results are as follows:

[0070] Finished product quality inspection After each processing step, the hardness, dimensional accuracy, and surface quality of the finished product were checked, and the test results are as follows:

[0071] Summarize Through multiple sets of comparative experiments, the processing technology of this invention, with optimization of parameters at each step, successfully controlled the machining accuracy, surface quality, and dimensional stability of bearing components. Data shows that this technology can significantly improve production efficiency while ensuring machining accuracy, and reduce material waste and machining defects during the manufacturing process.

[0072] Example 2: Effect of different freezing times on bearing machining results Experimental Background To further verify the adaptability and flexibility of the process of the present invention, Example 2 selected different low-temperature freezing times (24 hours, 48 ​​hours, and 72 hours) for comparative experiments, focusing on testing the impact of freezing treatment on the structural stability, cutting quality, and mechanical properties of the bearing components.

[0073] Experimental steps Low-temperature freezing treatment (S1): Objective: To evaluate the effects of different freezing times on the release of internal stress and the thermal stability of bearing components.

[0074] parameter: Freezing time: 24 hours, 48 ​​hours, 72 hours Freezing temperature: −20℃ (remain constant) Equipment: Use a temperature and humidity adjustable freezer, maintaining the relative humidity of the freezing environment at 20% to 40%.

[0075] Laser directional cutting (S2): Objective: To test the differences in cutting accuracy of accessories with different freezing times.

[0076] parameter: Laser power: 30 W Cutting speed: 7 mm / s Laser wavelength: 1064 nm Equipment: CNC laser cutting platform, path error controlled within ±0.05 mm.

[0077] Plasma cleaning process (S3): Objective: To evaluate the impact of different freezing treatments on surface cleanliness.

[0078] parameter: Gas volume ratio: Argon:Oxygen 9:1, Total flow rate: 250 mL / min Cleaning time: 10 minutes Plasma field strength: 50V Equipment: Plasma cleaning tank.

[0079] High-frequency heating and nano-spraying (S4): Objective: To perform surface enhancement treatment on components subjected to different freezing times.

[0080] parameter: Heating temperature: 300℃, Coating thickness: 30 μm Spraying air pressure: 0.3 MPa Equipment: High-frequency heater and gas spraying system.

[0081] Medium-temperature heat treatment (S5): Objective: To verify the performance of components with different freezing times during the heat treatment process.

[0082] parameter: Heat treatment temperature: 130℃, treatment time: 5 hours Equipment: Constant temperature chamber, with temperature fluctuations controlled within ±2℃.

[0083] High-temperature tempering and oil bath cooling (S6): Objective: To test the effects of different freezing treatments on tempering effect and dimensional stability of the final product.

[0084] parameter: Tempering temperature: 300℃, oil bath cooling temperature: 30℃ Cooling rate: 5℃ / min Equipment: High-temperature tempering chamber and oil tank cooling system.

[0085] Experimental Results and Performance Comparison The table below shows the experimental data on the effect of different freezing times on bearing machining. We paid particular attention to key performance indicators such as dimensional accuracy, surface quality, hardness, and cleanliness.

[0086]

[0087] Finished product quality inspection The hardness, dimensional accuracy, surface roughness, and surface cleanliness of the finished product were tested, and the results are as follows:

[0088] In summary, by comparing the effects of different freezing times on the processing results, it can be concluded that extending the freezing time to 48 hours and 72 hours improves the hardness and surface roughness of the finished product, especially demonstrating better stability and consistency in surface cleanliness and dimensional accuracy. The process of this invention, through precise control of low-temperature freezing time, can significantly optimize processing accuracy and finished product performance.

[0089] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A processing technology for a graphite-coated composite bearing with a tenon and mortise structure, characterized in that, Includes the following steps: Step S1) Low-temperature freezing treatment; Step S2) Laser directional cutting; Step S3) Plasma cleaning treatment; Step S4) High-frequency heating and nano-spraying; Step S5) Medium-temperature heat treatment; Step S6) High-temperature tempering and oil bath cooling treatment; Step S1) low-temperature freezing treatment includes: S11. Place all the metal parts of the tenon and mortise structure bearing into a freezer at a temperature of -18℃ to -25℃, and control the temperature of the parts to be uniform until the preset freezing temperature is reached. S12. Freezing time is not less than 24 hours to maintain material structural stability, release internal stress, and avoid deformation due to temperature difference. S13. Temperature fluctuations during the freezing process are controlled within ±1℃, and the freezing environment is maintained stable by a temperature and humidity control device. Step S2) laser directional cutting includes: S21. Place the frozen bearing parts on a CNC laser cutting platform, with an alignment error not exceeding 0.1 mm; S22. Perform high-precision cutting according to the drawings of the mortise and tenon structure, and control the path error within ±0.05 mm; S23, laser power is set to 20-50 W, cutting speed is 5-10 mm / s; S24. After cutting, a vision system and measuring instruments are used to check the accuracy of the cut surface, and the cut surface meets the design requirements. Step S3) plasma cleaning includes: S31. Place the cut bearing components into a plasma cleaning tank to fully expose their surfaces to the treatment area. S32. Set the cleaning power to 100-200 W and the time to 5-15 minutes. S33. After treatment, the surface cleanliness is confirmed by visual inspection and instrument testing. Step S4) High-frequency heating and nano-spraying includes: S41. Place the component into the high-frequency induction heater, set the heating temperature to 250-400℃, and the heating time to 5-10 minutes; S42. During the heating process, GC-901 nano-graphite material is sprayed using a gas spraying method; the thickness of the coating layer is controlled between 20 and 50 μm. S43. Allow to cool naturally to room temperature after spraying; The intermediate temperature heat treatment in step S5) includes: S51. Place the cooled components in a constant temperature chamber, set the temperature to 100-150℃, and maintain it for 4-6 hours. S52. Temperature fluctuations during the constant temperature process shall not exceed ±2℃; S53. After processing, the structural morphology and mechanical properties are tested. Step S6) High-temperature tempering and oil bath cooling treatment includes: S61. Place the parts treated at medium temperature into a high-temperature tempering chamber, set the temperature to 250-350℃, and the tempering time to 2-4 hours. S62. After tempering, transfer the parts into the oil bath. The oil temperature is controlled at 25-50℃ and the cooling rate is 5-10℃ / min. S63. After cooling, degreasing is performed using an environmentally friendly industrial cleaning agent. The surface moisture content is controlled below 0.5% after cleaning.

2. The processing technology for a graphite-coated composite bearing with a tenon and mortise structure according to claim 1, characterized in that: In step S13, three temperature monitoring points are set inside the freezer, located at different spatial positions of the bearing components, and the temperature fluctuation is controlled within ±0.5℃. The relative humidity in the freezing environment is maintained at 20% to 40%, and the humidity is controlled by the dehumidification module.

3. The processing technology for a graphite-coated composite bearing with a tenon and mortise structure according to claim 1, characterized in that: In step S22, the path error does not exceed ±0.03 mm; The laser wavelength is 1064 nm, the focused spot diameter is set to 60–80 μm, and the width of the heat-affected zone is monitored and controlled in real time within the range of 0.05–0.1 mm.

4. The processing technology for a graphite-coated composite bearing with a tenon and mortise structure according to claim 1, characterized in that: In step S32, the plasma cleaning uses a mixed gas of argon and oxygen in a volume ratio of 9:1 as the working medium, and the flow rate is controlled at 200-300 mL / min. Set the cleaning time to 10-15 minutes.

5. The processing technology for a graphite-coated composite bearing with a tenon and mortise structure according to claim 1, characterized in that: In step S42, the particle size of GC-901 nano-graphite material is less than 50 nm, the gas spraying pressure is set to 0.2-0.4 MPa, and the spraying distance is set to 25±2 cm. After spraying, the natural cooling time should be set to no less than 30 minutes.

6. The processing technology for a graphite-coated composite bearing with a tenon and mortise structure according to claim 1, characterized in that: In step S52, the workpiece surface temperature is sampled every 30 minutes.

7. The processing technology for a graphite-coated composite bearing with a tenon and mortise structure according to claim 1, characterized in that: In step S62, high-purity mineral oil is used for oil tank cooling, the oil temperature is set to 30±2℃, and the cooling time is set to 10 to 15 minutes; In step S63, the cleaning is performed using ultrasonic waves at a frequency of 40 kHz for 2 to 3 minutes. The drying process uses hot air at 45°C for 60 seconds, and the moisture content is controlled to be below 0.5%.

Citation Information

Patent Citations

  • Carbonitriding heat treatment method for air conditioner bearing ring

    CN105925931A

  • Machining method for cooling metal surface laser microtextures

    CN106392303A

  • Connecting rod with thermally sprayed bearing layer

    US6513238B1